Pheasants, Partridges & Grouse : Including buttonquails, sandgrouse and allies. - McGowan, Phil (Helm identification guides., 2010)
Covering almost 260 species of gamebirds, this book focuses on identification, status and distribution, habitats and geographical variation. Many of these species are both exotic and endangered, some are kept in private aviaries, while others are exploited commercially.